Inhibition of human colony-forming-unit erythroid by tumor necrosis factor requires accessory cells. - Means, R T (1990)
Recombinant tumor necrosis factor (rTNF) inhibits erythropoiesis in vivo and in vitro. To study the mechanism of this inhibition, the effect of rTNF on highly purified human CFU-erythroid (E) (mean purity 63.5%), which were generated from peripheral blood burst-forming units-erythroid (BFU-E), was compared to its effect on unpurified human marrow CFU-E (mean purity 0.21%). Although growth of colonies from marrow CFU-E was inhibited by rTNF, no significant effect on purified BFU-E-derived CFU-E colony growth was found. Removal of accessory marrow cells by soy bean agglutinin (SBA) ablated the inhibition of marrow CFU-E colonies by rTNF. Inhibition of colony growth was then restored by adding back SBA+ cells, but not by adding T lymphocytes or adherent cells. Conditioned medium prepared from bone marrow mononuclear cells stimulated by rTNF inhibited the growth of colonies from highly purified BFU-E derived CFU-E resistant to direct inhibition by rTNF. These findings indicate that rTNF does not directly inhibit CFU-E, but requires accessory cells to decrease erythropoiesis. These accessory cells reside in the SBA+ cell fraction, but are neither T cells nor adherent cells. Therefore, in order to produce anemia, TNF must induce release or production of a factor that directly inhibits erythroid colony growth.